LITERATURE REVIEW: REFLEKSI PEMIKIRAN KI HAJAR DEWANTARA TERKAIT FILOSOFI PENDIDIKAN DALAM SISTEM BELAJAR MENGAJAR DI INDONESIA - Anggraini Oktafiolita; Asri Wijiastuti (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Education is an important thing in Indonesia. Education can have an impact on the sustainable lives of students both in terms of character and social emotions. Apart from that, education can also help a student find his or her identity. This research aims to find out how suitable Ki Hajar Dewantara's thoughts are when applied in the world of education at all levels, both formal and non-formal, in Indonesia. The method used is Preferred Reporting Items For Systematic Reviews and Meta-analyses (PRISMA) which is taken from national journals and international journals. Searching for literature sources in this article via Google Scholar in 2013-2023. Based on the results of the study, it was found that the aim of Ki Hajar Dewantara's education, which was also instituted at Taman Siswa, was to produce ideal humans for the nation who were physically and spiritually healthy and had intellectual, emotional and intelligent abilities. all of which have been implemented in Indonesia and are still used as a reference for the teaching and learning process at all levels of formal and non-formal education. Ki Hajar Dewantara also through his opinion tries to emphasize the implementation of character education which must instill understanding, feel something learned and then implement it in real behavior which is now being implemented in Indonesia through continuously updated curricula